PENINGKATAN KUALITAS AIR MINUM MELALUI METODE PENYARINGAN BERTINGKAT BERBASIS LIMBAH KULIT TELUR DI DESA TERU KABUPATEN BANGKA TENGAH - Ristika Oktavia Asriza; Janiar Pitulima; Verry Andrei Fabiani; Robby Gus Mahardika (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2018)
In accordance Regulation Minister of Health Republic of Indonesia No. 492 / MENKES / PER / IV / 2010 about Quality Requirements of Water Drink, the acidity (pH) of water drink about 6.5 - 8. Based on situation analysis, Teru Village of Central Bangka Regency is below the standard, which about 4.1. The low pH of water drink in Teru village cause negative effect for health. So, an effort to improve the quality of water drink is needed. Through IbM Devotion of Society was created by filtration tool on eggshell-based waste in Teru Village, Central Bangka Regency. By utilizing an egg shell waste containing calcium carbonate, it is expected to increase the pH of the water. Based on the results of trials in the field, the results obtained that there was an increase in the pH of water drink to 6.91, which is in accordance with drinking water quality standard.